Study of Physical Water Loss in Water Distribution Network using Step Test Method and Pressure Calibration - Azwar, Erizaldy; Irawan, Diki Surya; Naufal, Muhammad (Universitas Tribhuwana Tunggadewi Malang, 2021)
Water distribution networks that are unoptimally operated can cause various problems so that water flows are not evenly distributed to consumers. One of the causes is the high water loss level due to leaks in the distribution pipeline system, as one of the water operators in Jakarta, Indonesia, PT. XYZ has tremendous efforts to improve the water supply system. One of them is to reduce physical water losses. The estimated percentage of physical water losses of water distribution networks in Green Garden District, West Jakarta, in April 2018 has amounted to 30%. It is still above the tolerance standard for the national water loss rate in Indonesia's Water Utilities, around 20%. It is necessary to reduce water loss to overcome this problem. After performing a step test program in the Green Garden District, it was found that there was a water loss of 84 lps in July 2018, which increased to 103.16 l/sin in May 2019 or showed an increase of 23%. Then, a pressure calibration was undertaken by placing six pressure monitoring points on the district in May 2019 using hydraulic simulation from WaterGEMS V.10. This calibration obtained the highest pressure Gap at pressure monitoring point #5 of 2.5 mH2O and the lowest pressure monitoring point #1 of 1.03 mH2O. Subsequently, leak detection measures were conducted to reduce physical water loss from January to May 2019, PT. XYZ water distribution network uses two leak detection methods, visible and invisible leak detections, which had successfully reduced its net night flows (NNFs). The leak repairs obtained 77 leak points, which consisted of 32 visible leaks and 45 invisible leaks. Total estimated leakage flows of 5.33 lps were obtained from the decrease in the net night flow, which indicates a decrease in physical water loss by 16% from January to March 2019.